Reactive Oxygen Species (ROS), Intimal Thickening, and Subclinical Atherosclerotic Disease - Burtenshaw, Denise; Kitching, Michael; Redmond, Eileen M.; Megson, Ian L.; Cahill, Paul A. (Frontiers in Cardiovascular Medicine, 2019)
Arteriosclerosis causes significant morbidity and mortality worldwide. Central to this process is the development of subclinical non-atherosclerotic intimal lesions before the appearance of pathologic intimal thickening and advanced atherosclerotic plaques. Intimal thickening is associated with several risk factors, including oxidative stress due to reactive oxygen species (ROS), inflammatory cytokines and lipid peroxidation. The main ROS producing systems in-vivo are reduced nicotinamide dinucleotide phosphate (NADPH) oxidase (NOX). ROS effects are context specific. Exogenous ROS induces apoptosis and senescence, whereas intracellular ROS promotes stem cell differentiation, proliferation and migration. Lineage tracing studies using murine models of subclinical atherosclerosis have revealed the contributory role of medial smooth muscle cells (SMCs), resident vascular stem cells, circulating bone-marrow progenitors and endothelial cells that undergo endothelial-mesenchymal-transition (EndoMT). This review will address the putative physiological and patho-physiological roles of ROS in controlling vascular cell fate and ROS contribution to vascular regeneration and disease progression.